Conflict Management in All-Day Small Rural and One-Age Classroom Primary Schools - Τσιπά Σπυριδούλα; Αθανασούλα-Ρέππα Αναστασία (Education Sciences, 2021)
To investigate the behavior of leaders and/or potential leaders in conflict management in all-day primary schools was the basis of the study. The descriptive analysis demonstrated that respondents follow exactly the same trend of choice in small rural and one-age classroom, with dominant conflict management compromising style, to a lesser extent some avoiding practices and lastly the competing style. The comparative study revealed a difference in the selection range of choice of the conflict management style for sub-headmasters versus headmasters and teachers, who adopt competing style as second choice, confirming the scientific consideration of the ΄backup style΄ that the sub-directory follows. Also, it turns out that only about avoiding style differ statistically average values ​​of the respondents perceptions in small rural compared to those in one-age classroom primary schools. Admittedly, the adoption of management- compromise practices versus moderate and dynamic practices by respondents is encouraging, but it is equally important that the management of in-school conflicts to consider each case in the specific socio-cultural context and prevailing school culture.